Finnish open university education and students’ transitions into and within higher education - Isopahkala-Bouret, Ulpukka; Haltia, Nina (University of Borås, 2025)
There is a growing number of higher education (HE) students who do not follow the conventional sequential progression from the beginning to the end of their studies. Instead, they may use alternative admission routes, take gap years, delay their studies and transfer from one discipline or institution to another. In particular, students from under-represented social groups tend to follow less linear trajectories. In this article, we are interested in the institutional policies and practices that enable multiple ways for students to navigate into and within HE. As a theoretical lens, we apply Gale and Parker’s typology of student transition and the conceptualisation of transition as ‘becoming,’ which entails rejecting the notion of linearity and normativity. Our empirical case is Finnish open university education (OUE). Using student interviews (N=16) and reflexive thematic analysis, we identified three institutional characteristics: openness of access, flexible mode of studies, and alternative access route to degree studies. These characterisics enabled highly individualised learning trajectories and opportunity to enter, withdraw and return to OUE throughout life. However, the OUE gateway was selective, which limited its potential to reduce social inequality in student transitions. The study advances the policy discussion and development of inclusive universities.